Doppler hemodynamic evaluation of prosthetic (Starr-Edwards and Björk-Shiley) and Bioprosthetic (Hancock and Carpentier-Edwards) cardiac valves - Williams, George A.; Labovitz, Arthur J. (The American journal of cardiology, 1985)
One hundred thirty-four patients with prosthetic or bioprosthetic heart valves were investigated with Doppler echocardiography to determine normal values for commonly used prosthetic valves and to test the specificity of abnormal Doppler findings. In 70 patients the aortic valves had been replaced and in 64 the mitral valves had been replaced. Gradients across prostheses in the aortic position were calculated from maximal velocity. Peak calculated aortic transvalvular gradients in normal subjects were 22 ± 10 mm Hg in 33 Björk-Shiley valves, 23 ± 10 mm Hg in 27 porcine valves and 29 ± 13 mm Hg in 6 Starr-Edwards valves. Mild aortic regurgitation was seen in 42% of Björk-Shiley valves, 26% of porcine valves and 2 of 6 Starr-Edwards valves. Mitral valve orifice was calculated by the pressure half-time method. In clinically normal patients with mitral valve prostheses, the effective mitral valve orifice was 2.5 ± 0.8 cm 2 in 35 Björk-Shiley valves, 2.1 ± 0.7 cm 2 in 17 porcine valves, and 2.0 ± 0.3 cm 2 in 10 Starr-Edwards valves. Mitral regurgitation was found in 11% of Björk-Shiley valves, 19% of porcine valves and 30% of Starr-Edwards valves. Repeat studies at 2 weeks to 14 months revealed no difference in 8 aortic and 14 mitral prostheses. Seven aortic and 4 mitral valves functioned abnormally as determined by Doppler, and the abnormal function was confirmed in each at surgery or at cardiac catheterization. Hemodynamic measurements by Doppler provide noninvasive information similar to that provided by cardiac catheterization that is reproducible and specific for valve dysfunction. Doppler echocardiography is a valuable adjunct to the noninvasive assessment of prosthetic and bioprosthetic heart valves.